Dielectric barrier discharge coupling catalytic oxidation for efficient conversion of Hg0 from flue gas. (1st March 2021) - Cui, Shaoping; Liao, Yujie; Gao, Zhengyang; Fu, Dong
Graphical abstract: Highlights: A new approach was proposed for the conversion of elemental mercury (Hg 0 ). Effects of operation conditions on Hg 0 conversion efficiency were illustrated. Reaction mechanism and conversion path of Hg 0 were inferred. Higher efficiency and lower energy consumption were achieved. The applied method has good application potential in the field of Hg 0 conversion. Abstract: For efficient conversion of elemental mercury (Hg 0 ) in flue gas, we coupled the non-thermal plasma (NTP) and catalytic oxidation, and prepared MnCu/Ti catalytic through dielectric barrier discharge (DBD) reactor. The experimental system of DBD coupling MnCu/Ti catalytic oxidation was established. The catalytic oxidation performance and the influences of energy density (SED), oxygen content, H2 O content, and the concentrations of NO and SO2 on the conversion efficiency of Hg 0 were clarified. Based on the experimental results and DFT simulation results, the mechanism of the catalytic oxidation was elucidated. Our results showed that after coupling with MnCu/Ti, the conversion efficiency of Hg 0 in DBD reactor under mild conditions increased from 42.9% to 86.7%, and the energy consumption decreased from 0.77 mg Hg 0 /kWh to 1.56 mg Hg 0 /kWh. The proposed method has the advantages of high efficiency, intensive and no secondary pollution, hence it has good application potential in Hg 0 conversion and removal from flue gas.